Ruy Fausto on Understanding, Reason, and the Limits of Dialectics (Revista Eletrônica Estudos Hegelianos, 2024)
This paper explores the differences between Hegelian and Marxian dialectics in Ruy Fausto’s project to reconstitute dialectical logic. First, it considers his reading of the relationship between understanding and reason in Hegel and Marx, with priority given to the treatment of the Science of Logic and Capital. Then, it shows how Fausto’s so-called interiorizing and exteriorizing movements in Marx’s logical presentation of the forms of capital lead to a new view of the system that coincides with its critique, thus subverting the positive direction of modern dialectics and the systematicity of reason. Finally, in the light of these results, it presents Fausto’s idea of the limits of dialectics in Marx and its negative character.